Effects and mechanisms of tea for the prevention and management of cancers: An updated review - Xu, Xiao-Yu; Zhao, Cai-Ning; Cao, Shi-Yu; Tang, Guo-Yi; Gan, Ren-You; Li, Hua-Bin (Critical reviews in food science and nutrition, 2020)
Tea is a traditional and popular beverage worldwide, and the consumption of tea has been demonstrated to possess many health benefits, such as cardiovascular protection, anti-obesity, anti-diabetes, and anticancer. Epidemiological studies have shown that the consumption of tea is inversely associated with the risk of several cancers. In addition, experimental studies have revealed that the anticancer actions of tea are mainly attributed to tea polyphenols, such as epigallocatechin-3-gallate and theaflavins. Both in vitro and in vivo studies have demonstrated that the possible anticancer mechanisms are the inhibition on proliferation, anti-angiogenesis, induction of apoptosis, suppression on metastasis, inhibition on cancer stem cells, and modulation on gut microbiota. Its synergetic anticancer effects with drugs or other compounds could promote anticancer therapies. Furthermore, clinical trials have elucidated that intervention of tea phytochemicals is effective in the prevention of several cancers. This paper is an updated review for the prevention and management of cancers by tea based on the findings from epidemiological, experimental and clinical studies, and special attention is paid on the mechanisms of action.